GEOMETRIC ORNAMENT IN ISLAMIC ART: TRADITIONS, FEATURES, COMPONENTS - Аззаарі, Алі (Art and Design, 2021)
Purpose of the article аnalyze the features of Islamic geometric ornament as a historical and at the same time modern artistic phenomenon, its formation, development, traditional structural elements. Methodology. General scientific research methods, chronological and historical ‒ comparative, figurative-stylistic, semantic, and theoretical-art history analysis are applied. Results. The features of the historical development of geometric ornament in the countries of Islam, its national, historical, mental, figurative, artistic features are analyzed. Recognized in the world as a unique work of art, Islamic geometric ornament is known for its compositional construction which consists of simple elements (circle, square, triangle). Then by connecting and repeating the shapes according to a certain grid pattern, a complex pattern (hexagon, octagon, star pattern) is created. The richness of the artistic culture of Islam is embodied in the range of its variants. It was found that the geometric ornament, which is the main decorative element on numerous objects, embodies a deep spiritual content. Geometric Islamic ornament embodies thousands of years of creative practice that has become traditional in the Arab East. At the same time, in the modern world, Muslim ornamental traditions remain relevant and reveal opportunities for introducing the acquired artistic experience of the Arab countries into new creative practices, including graphic design. Scientific novelty consists in determining the place and significance of Islamic geometric ornament in modern cultural and historical processes, taking into account its traditional aesthetic, substantial, structural and compositional content. Practical significance. The proposed research expands the understanding of the possibilities of using the traditions of Islamic ornament in modern creative practices. The results can be used in design practice.